Preparation method of solid oxide fuel cell

CN119447387APending Publication Date: 2025-02-14CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411412057.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

During the sintering process, the residual stress occurs due to the difference in thermal expansion coefficient, which affects its long life and stable service.

Method used

By optimizing the process flow and parameters, a sintering method of multiple heating and cooling is adopted, combined with co-sintering and separate sintering processes, the in-situ control of residual stress is achieved.

Benefits of technology

It effectively reduces the residual stress of SOFC, improves surface flatness, assembly accuracy, elastic modulus and bending strength, and enhances electrochemical performance, including improving battery stability, reducing internal resistance and polarization impedance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447387A_ABST
    Figure CN119447387A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a solid oxide fuel cell, and belongs to the technical field of fuel cells. The method comprises the following steps: (1) preparing an anode support body through primary tape casting; (2) sequentially carrying out silk-screen printing on an anode functional layer and an electrolyte layer on the anode support body, and carrying out degumming and co-sintering to form a half cell; (3) carrying out silk-screen printing on a barrier layer on the half cell, and sintering; (4) carrying out silk-screen printing on a transition layer and a composite cathode layer on the barrier layer, and carrying out co-sintering to obtain a single cell; the sintering process in the steps comprises the following steps: firstly, heating to a sintering temperature in a multi-time heating manner for sintering, and then cooling to the room temperature in a multi-time cooling manner. In the preparation process of the fuel cell, the residual stress is controlled in situ by optimizing the technological process and parameters, so that the surface flatness is higher, the residual stress is reduced, and the failure probability is reduced; the electrochemical performance is also improved, so that the battery has a low grain boundary resistance value and high ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cell preparation, and in particular to a method for preparing a solid oxide fuel cell. Background Art

[0002] Solid oxide fuel cell (SOFC) is an electrochemical device that converts chemical energy in fuel directly into electrical energy. It has the advantages of high energy conversion rate, low emission, low noise and fuel flexibility. It has broad application prospects in military equipment and civil fields such as large centralized power supply, medium-sized power distribution and small household cogeneration as fixed power stations, as well as mobile power sources such as ship power supply and transportation vehicle power supply. SOFC is often formed by multiple processes such as casting, screen printing and sintering, and contains more than 3 layers of structure. The material preparation is relatively simple, but due to the difference in chemical composition of each layer structure, residual stress is inevitably generated after the preparation is completed due to the difference in thermal expansion coefficient during the sintering process. The existence of sintering residual stress has a great influence on the long-life stable service of SOFC. Reducing sintering residual stress is the most effective way to improve the service reliability of SOFC. However, due to the small size of SOFC and high deformation requirements, it is impossible to reduce the sintering residual stress by post-processing methods. Based on this, a solid oxide fuel cell preparation method with in-situ control of sintering residual stress is proposed. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a method for preparing a solid oxide fuel cell, which realizes in-situ control of residual stress by optimizing the process flow and parameters during the preparation of the fuel cell.

[0004] The technical solution adopted by the present invention is:

[0005] The present invention provides a method for preparing a solid oxide fuel cell, comprising the steps of:

[0006] (1) preparing an anode support slurry, and preparing an anode support by a single casting process, and cutting the anode support according to size requirements after the anode support is formed;

[0007] (2) forming an anode functional layer and an electrolyte layer by screen printing an anode functional layer slurry and an electrolyte slurry on the cut anode support in sequence, and forming a half-cell consisting of an anode support, an anode functional layer and an electrolyte layer by debinding and co-sintering;

[0008] (3) screen printing a barrier layer slurry on the sintered half-cell to form a barrier layer, and sintering the half-cell;

[0009] (4) screen-printing a transition layer slurry and a composite cathode layer slurry on the sintered barrier layer in sequence to form a transition layer and a composite cathode layer, and co-sintering them to obtain a solid oxide fuel cell cell;

[0010] The sintering process in steps (2), (3) and (4) is specifically as follows: firstly, the temperature is raised to the sintering temperature by multiple heating methods for sintering, and then the temperature is lowered to room temperature by multiple cooling methods.

[0011] Furthermore, in the step (1), the anode support slurry is made of NiO-8YSZ, and the thickness of the anode support is 300-500 μm.

[0012] Furthermore, in the step (2), the anode functional layer slurry is made of NiO-8YSZ, and the thickness of the anode functional layer is 15 to 30 μm.

[0013] Furthermore, in step (2), the electrolyte slurry is YSZ, and the thickness of the electrolyte layer is 10 to 15 μm.

[0014] Furthermore, in step (3), the barrier layer slurry is GDC, and the thickness of the barrier layer is 8 to 10 μm.

[0015] Furthermore, in step (4), the transition layer slurry is LSCF and GDC, the mass ratio of LSCF and GDC is 1:1, the thickness of the transition layer is 5 to 20 μm, and the composite cathode layer slurry is made of LSCF and GDC, the mass ratio of LSCF and GDC is 1:1, and the thickness of the composite cathode layer is 30 to 40 μm.

[0016] Furthermore, the debinding and co-sintering process in step (2) is specifically as follows:

[0017] First, the temperature is increased to 500-550°C at a heating rate of 2-4°C / min, and the temperature is kept for 2-5 hours to perform debinding; then the temperature is increased to 1000-1100°C at a heating rate of 5-8°C / min, and the temperature is kept for 4-10 hours; then the temperature is increased to 1300-1350°C at a heating rate of 4-6°C / min, and a pressure of 0.4-0.5MPa is applied, and the temperature is kept for 1-3 hours; then the temperature is reduced in three stages: in the first stage, the pressure is maintained at 0.4-0.5MPa, and the temperature is slowly reduced to 1000-1100°C at a cooling rate of 2-4°C / min; in the second stage, the loading pressure is removed, and the temperature is reduced to 400-500°C at a cooling rate of 4-6°C / min; in the third stage, the temperature is reduced to room temperature by natural cooling.

[0018] Furthermore, the sintering process of the barrier layer in step (3) is specifically as follows:

[0019] First, heat the temperature to 450-500°C at a heating rate of 3-5°C / min and keep it at that temperature for 1-5h; then heat the temperature to 1200-1250°C at a heating rate of 5-8°C / min and keep it at that temperature for 3-6h; then cool down in three stages: the first stage is to slowly cool down to 800-900°C at a cooling rate of 1-3°C / min, the second stage is to cool down to 400-500°C at a cooling rate of 5-7°C / min, and the third stage is to cool down to room temperature by natural cooling.

[0020] Furthermore, the sintering process of the transition layer and the composite cathode layer in step (4) is specifically as follows:

[0021] First, heat the temperature to 450-500°C at a heating rate of 3-5°C / min and keep it at that temperature for 1-5h; then heat the temperature to 1050-1100°C at a heating rate of 5-8°C / min and keep it at that temperature for 3-8h; then cool down in two stages: the first stage is to cool down to 400-500°C at a cooling rate of 3-5°C / min, and the second stage is to cool down to room temperature by natural cooling.

[0022] The beneficial effects of the present invention are:

[0023] The present invention provides a method for preparing a solid oxide fuel cell. During the preparation of the fuel cell, in-situ residual stress is controlled by optimizing the process flow and parameters, so that the surface flatness is higher, the assembly accuracy is improved, the elastic modulus is increased, the bending strength is increased, and the failure probability is reduced; at the same time, the electrochemical performance is further improved, that is, the battery stability is improved, and the battery has a low grain boundary resistance and high ionic conductivity, thereby reducing the polarization impedance, increasing the peak power density, and reducing the internal resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 This is a flow chart of Embodiment 1 of the present invention;

[0026] Figure 2 is a process curve of the half-cell co-sintering process of Example 1 of the present invention;

[0027] Figure 3 is a process curve of the sintering process of the barrier layer in Example 1 of the present invention;

[0028] Figure 4 is a process curve of the co-sintering process of the transition layer and the composite cathode layer in Example 1 of the present invention;

[0029] Figure 5 A microstructure diagram of the local structure of a single cell prepared in Example 1 of the present invention;

[0030] Figure 6 The voltage-current curves of the single cells prepared in Example 1 and Comparative Example 1;

[0031] Figure 7 The bending strength variation curves of the single cells prepared in Example 1 and Comparative Example 1;

[0032] Figure 8 The elastic modulus change curves of the single cells prepared in Example 1 and Comparative Example 1;

[0033] Fig. 9 The residual stress variation curves of the single cells prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0034] The present invention provides a method for preparing a solid oxide fuel cell. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0035] The present invention is described in detail below with reference to the accompanying drawings.

[0036] Example 1

[0037] Reference Figures 1 to 4 , this embodiment provides a method for preparing a solid oxide fuel cell, wherein the solid oxide fuel cell is stacked by a plurality of layers of single cell sheets, a sealing layer and a connector, and each layer of single cell sheets includes an anode support, an anode functional layer, an electrolyte layer, a barrier layer, a transition layer and a composite cathode layer. Among them, the anode support is made of NiO-8YSZ, and the thickness of the anode support is 500μm; the anode functional layer is made of NiO-8YSZ, and the thickness of the anode functional layer is 20μm; the electrolyte layer is YSZ, and the thickness of the electrolyte layer is 15μm; the barrier layer is GDC, and the thickness of the barrier layer is 10μm; the transition layer is made of LSCF and GDC, and the thickness of the transition layer is 20μm; the composite cathode layer is made of LSCF and GDC, and the mass ratio of LSCF and GDC is 1:1, and the thickness of the composite cathode layer is 40μm.

[0038] The specific steps are as follows:

[0039] (1) preparing the corresponding anode support, anode functional layer, electrolyte layer, barrier layer, transition layer, and composite cathode layer slurry according to the materials of the above-mentioned single cell sheet structure, preparing the anode support by one-time casting, and cutting it according to the size requirements after it is formed. When preparing the anode support, it is necessary to ensure the consistency of the anode support slurry with the casting environment temperature and the uniformity of the slurry;

[0040] (2) on the cut anode support, an anode functional layer slurry and an electrolyte slurry are sequentially screen-printed to form an anode functional layer and an electrolyte layer, and a half-cell consisting of an anode support, an anode functional layer and an electrolyte layer is formed by debinding and co-sintering; the debinding and co-sintering process is specifically as follows: first, the temperature is raised to 550°C at a heating rate of 3°C / min, and the temperature is kept at this temperature for 3 hours to debind; then, the temperature is raised to 1100°C at a heating rate of 6°C / min, and the temperature is kept at this temperature for 6 hours; then, the temperature is raised to 1350°C at a heating rate of 5°C / min, and a pressure of 0.4-0.5MPa is applied, and the temperature is kept at this temperature for 2 hours; then, the temperature is cooled in three stages: in the first stage, a pressure of 0.4-0.5MPa is maintained, and the temperature is slowly cooled to 1100°C at a cooling rate of 3°C / min; in the second stage, the loading pressure is removed, and the temperature is cooled to 500°C at a cooling rate of 5°C / min; in the third stage, the temperature is cooled to room temperature by natural cooling;

[0041] (3) Screen printing a barrier layer slurry on the sintered half-cell to form a barrier layer, and sintering; the sintering process is specifically as follows: first, heating to 500°C at a heating rate of 4°C / min, and keeping at that temperature for 2 hours; then heating to 1250°C at a heating rate of 6°C / min, and keeping at that temperature for 4 hours; then cooling in three stages: the first stage is slowly cooled to 900°C at a cooling rate of 2°C / min, the second stage is cooled to 500°C at a cooling rate of 6°C / min, and the third stage is cooled to room temperature by natural cooling;

[0042] (4) Screen printing a transition layer slurry and a composite cathode layer slurry on the sintered barrier layer in sequence to form a transition layer and a composite cathode layer, and co-sintering to obtain a solid oxide fuel cell single cell sheet; the sintering process is specifically as follows: first, heating to 500°C at a heating rate of 4°C / min and keeping warm for 3 hours; then heating to 1100°C at a heating rate of 6°C / min and keeping warm for 4 hours; then cooling in two stages: the first stage is cooling to 500°C at a cooling rate of 4°C / min, and the second stage is cooling to room temperature by natural cooling.

[0043] In the above-mentioned preparation process of this embodiment, a method of multiple heating and multiple cooling sintering is adopted. This is because during the sintering process, the material will expand and contract due to temperature changes, and residual stress is often generated in a single heating or cooling process. By adopting the method of multiple heating and cooling, the material can gradually adapt to the changes in thermal expansion or contraction in the small temperature difference in each stage, thereby reducing sudden stress accumulation. Moreover, this staged temperature change allows the material to deform under a relatively low stress state, which helps to balance the stress inside the material, reduce the risk of brittle fracture caused by too rapid temperature changes, and improve the overall uniformity and stability of the material.

[0044] In the above preparation process of this embodiment, the anode layer and the electrolyte layer are co-sintered, and the temperature is lowered by pressurization during the cooling process after sintering. The co-sintering method helps to achieve good bonding between the layers, reduce interface stress, and effectively reduce stress concentration between layers, improve the bonding strength between different material layers, and thus improve the cycle stability of the battery; applying pressure during cooling can offset the stress caused by temperature changes, promote uniform distribution of stress, and in the process of pressurization and cooling, it can more effectively fix the microstructure of the material and reduce the risk of crack formation.

[0045] In the above preparation process of this embodiment, the barrier layer is sintered separately. The independent sintering of the barrier layer can separate its own heat treatment conditions from other layers of the battery, thereby reducing the stress caused by the difference in thermal expansion coefficients of different materials. By optimizing the sintering process of the barrier layer, the internal stress state can be reduced. Moreover, sintering the barrier layer separately and optimizing the sintering process also reduce the stress transfer between the barrier layer and the electrolyte or anode, which helps to improve the stability of the entire battery and reduce the failure mechanism caused by material mismatch.

[0046] In the above preparation process of this embodiment, the transition layer and the composite cathode layer are co-sintered. This is because the transition layer exists to buffer the thermal and mechanical mismatch between the cathode and the electrolyte. Co-sintering can achieve better contact and stress dispersion between the two layers, and further reduce the interface stress between the materials. At the same time, through the action of the transition layer, the effect of the brittle materials of different materials on the stress of other regions is reduced, thereby improving the reliability and overall performance of the battery interface.

[0047] Through the above-mentioned preparation process, this embodiment can effectively release the residual stress inside the battery, thereby improving the performance reliability and durability of the fuel cell; and reducing the residual stress will also help improve the cycle stability of the battery, extend the service life, and create good conditions for the stable operation of the battery under high load.

[0048] The microstructure of the single cell prepared above was detected by scanning electron microscopy. The local microstructure of the single cell is as follows: Figure 5As shown, through Figure 5 It can be seen that the single cell has an obvious 6-layer structure, and the layers are closely connected.

[0049] Comparative Example 1

[0050] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, a transition layer slurry is first screen-printed on the sintered barrier layer to form a transition layer, and then sintered; and then a composite cathode layer slurry is screen-printed to form a composite cathode layer, and then sintered to obtain a solid oxide fuel cell cell, and the sintering process parameters are the same as those in Example 1.

[0051] The power generation performance of the single cell prepared in Example 1 is compared with that of the single cell prepared in Comparative Example 1. Figure 6 As shown. Figure 6 It can be seen that the power generation performance of the single cell prepared in the above Example 1 is better than that in Comparative Example 1, and Example 1 has a high peak power density and a lower internal resistance.

[0052] The mechanical properties of the single cell prepared in Example 1 and the single cell prepared in Comparative Example 1 are compared. Figure 7 and Figure 8 As shown, Figure 7 is the bending strength test result, Figure 8 is the elastic modulus test result, Fig. 9 is the residual stress test result. Figure 7 and Figure 8 It can be seen that the bending strength and elastic modulus of the single cell prepared in Example 1 are better than those in Comparative Example 1. Fig. 9 It can be seen that the residual stress of the single cell prepared in the above Example 1 is smaller than that in Comparative Example 1, and in-situ control of the residual stress is achieved.

[0053] It should be noted that some parts not described in the present invention can be implemented by adopting or drawing on existing technologies.

[0054] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A method for preparing a solid oxide fuel cell, characterized in that: Includes steps: (1) preparing an anode support slurry, and preparing an anode support by a single casting process, and cutting the anode support according to size requirements after the anode support is formed; (2) forming an anode functional layer and an electrolyte layer by screen printing an anode functional layer slurry and an electrolyte slurry on the cut anode support in sequence, and forming a half-cell consisting of an anode support, an anode functional layer and an electrolyte layer by debinding and co-sintering; (3) screen printing a barrier layer slurry on the sintered half-cell to form a barrier layer, and sintering the half-cell; (4) screen-printing a transition layer slurry and a composite cathode layer slurry on the sintered barrier layer in sequence to form a transition layer and a composite cathode layer, and co-sintering them to obtain a solid oxide fuel cell cell; The sintering process in steps (2), (3) and (4) is specifically as follows: firstly, the temperature is raised to the sintering temperature by multiple heating methods for sintering, and then the temperature is lowered to room temperature by multiple cooling methods.

2. A method for preparing a solid oxide fuel cell according to claim 1, characterized in that: In the step (1), the anode support slurry is made of NiO-8YSZ, and the thickness of the anode support is 300-500 μm.

3. A method for preparing a solid oxide fuel cell according to claim 1, characterized in that: In the step (2), the anode functional layer slurry is made of NiO-8YSZ, and the thickness of the anode functional layer is 15 to 30 μm.

4. A method for preparing a solid oxide fuel cell according to claim 1, characterized in that: In the step (2), the electrolyte slurry is YSZ, and the thickness of the electrolyte layer is 10 to 15 μm.

5. The method for preparing a solid oxide fuel cell according to claim 1, characterized in that: In the step (3), the barrier layer slurry is GDC, and the thickness of the barrier layer is 8 to 10 μm.

6. A method for preparing a solid oxide fuel cell according to claim 1, characterized in that: In the step (4), the transition layer slurry is made of LSCF and GDC, the mass ratio of LSCF and GDC is 1:1, the thickness of the transition layer is 5 to 20 μm, and the composite cathode layer slurry is made of LSCF and GDC, the mass ratio of LSCF and GDC is 1:1, and the thickness of the composite cathode layer is 30 to 40 μm.

7. A method for preparing a solid oxide fuel cell according to claim 1, characterized in that: The debinding and co-sintering process of the anode support, the anode functional layer and the electrolyte layer in step (2) is specifically as follows: First, the temperature is increased to 500-550°C at a heating rate of 2-4°C / min, and the temperature is kept for 2-5 hours to perform debinding; then the temperature is increased to 1000-1100°C at a heating rate of 5-8°C / min, and the temperature is kept for 4-10 hours; then the temperature is increased to 1300-1350°C at a heating rate of 4-6°C / min, and a pressure of 0.4-0.5MPa is applied, and the temperature is kept for 1-3 hours; then the temperature is reduced in three stages: in the first stage, the pressure is maintained at 0.4-0.5MPa, and the temperature is slowly reduced to 1000-1100°C at a cooling rate of 2-4°C / min; in the second stage, the loading pressure is removed, and the temperature is reduced to 400-500°C at a cooling rate of 4-6°C / min; in the third stage, the temperature is reduced to room temperature by natural cooling.

8. The method for preparing a solid oxide fuel cell according to claim 1, characterized in that: The sintering process of the barrier layer in step (3) is specifically as follows: First, heat the temperature to 450-500°C at a heating rate of 3-5°C / min and keep it at that temperature for 1-5h; then heat the temperature to 1200-1250°C at a heating rate of 5-8°C / min and keep it at that temperature for 3-6h; then cool down in three stages: the first stage is to slowly cool down to 800-900°C at a cooling rate of 1-3°C / min, the second stage is to cool down to 400-500°C at a cooling rate of 5-7°C / min, and the third stage is to cool down to room temperature by natural cooling.

9. A method for preparing a solid oxide fuel cell according to claim 1, characterized in that: The sintering process of the transition layer and the composite cathode layer in step (4) is specifically as follows: First, heat the temperature to 450-500°C at a heating rate of 3-5°C / min and keep it at that temperature for 1-5h; then heat the temperature to 1050-1100°C at a heating rate of 5-8°C / min and keep it at that temperature for 3-8h; then cool down in two stages: the first stage is to cool down to 400-500°C at a cooling rate of 3-5°C / min, and the second stage is to cool down to room temperature by natural cooling.